Study in Teaching Experience's School for Students in The Institute of Physical Education Lampang Campus - คงอุไร และคณะ, อุมาภรณ์ (Academic Journal of Thailand National Sports University, 2010)
This research consisted of two parts as followed: Part 1, The purpose of this research was to evaluate the school health program activities in schools that accepted the students from the Physical Education Institute Lampang Campus as teacher trainees for Work Experience Practice by the studying the population were 39 administrators 39 and supervising teachers and 52 teacher trainee students. The tool used in collecting the data was a questionnaire concerning the school health program activities. The research findings were: The perception concerning of the school health policies according to the administrators, supervising teachers and students was form significantly different at the .05 level The opinions concerning the administration of the school health program according to the administrators, the supervising teachers and students were found significantly different at the .05 level The opinions of the administrators, the supervising teachers and the students concerning the management of the healthful school environment were found no significant differences at the .05 level For the health service, the opinions of the administrators, supervising teachers and students differed were found significantly different at the .05 level For school health education, the opinions of the administrators, supervising teachers and students were found no significant differences at the .05 level The opinions concerning the need for skills and abilities of physical education students in the work experience practice in school health programs among the administrators, the supervising teachers and students were found no significant differences at the .05 level Part 2 From the school health program reports, the research team ranked the problems according to their levels of importance to plan for a workshop to develop additional skills and abilities for students by specifying the framework for the workshop seminar for the students and supervising teachers from the work experience practice school network then evaluated the developments of students in the school health program activity execution by asking the opinions of the administrators and the supervising teachers totaled 58 persons and 43 teacher trainee students and found that: The development of knowledge and abilities in the development of school health program activities in all three factors, according to the opinions of the administrators, the supervising teachers and the students was at the level high. The development of other knowledge and abilities essential to the teacher profession was at the level High. The development in the project execution was at the level high. 4. The development in the classroom research was at the level high. The opinion's satisfaction of school health program activity execution was at the high level.